New Plants for Florida: Grain - Ron Barnett; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
Grain crops are widely grown in the Southeast for forage production, grain, and cover crops. They provide green livestock forage during the late fall, winter and early spring months when permanent pastures are generally dormant and nonproductive. Many successful varieties of grain have been released by the FAES Grain Breeding Team. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.